Modeling and dynamic analysis of a battlefield water filtration station considering road surface profiles - To Viet, Thanh (Journal of Military Science and Technology, 2025)
During battlefield operations, mobile water filtration stations are used to supply clean water to military units, one of which is the VFS-2.5 filtration station. When in motion, it tows a trailer carrying a generator and chemical tanks for water filtration. The dynamic model, constructed as a multi-body system, is developed as a planar model with a two-axle truck as the towing vehicle. The study considers the elasticity of the suspension system, tires, and trailer hitch while neglecting the influence of road slope. Based on the dynamic model, the Lagrange equation of the second kind is used to establish the system of differential equations describing the motion of the system. The research model can be utilised to evaluate the stability of the water filtration station, and the aim is to improve the suspension system on the generator trailer to minimise the vibrations of the assembly. This is a highly significant issue in the field of national defence and security.